Craniofacial structures' development in prenatal period: An MRI study. (13th March 2018) - Begnoni, G.; Serrao, G.; Musto, F.; Pellegrini, G.; Triulzi, F. M.; Dellavia, C.
Structured Abstract: Introduction: The development of skeletal structures (cranial base, upper and lower) and upper airways spaces (oropharyngeal and nasopharyngeal) of the skull has always been an issue of great interest in orthodontics. Foetal MRI images obtained as screening exam during pregnancy can help to understand the development of these structures using a sample cephalometric analysis. Material and Methods: A total of 28 MRI images in sagittal section of foetuses from 20th to 32th weeks of gestation were obtained to dispel doubts about the presence of skeletal malformations. Cephalometric measurements were performed on MRI T2‐dependent images acquired with a 1.5 T scanner. The Software Osirix 5 permits to study sagittal and vertical dimensions of the skull analysing linear measurements, angles and areas of the skeletal structures. Results: Vertical and sagittal dimension of cranial base, maxilla and mandible grow significantly ( P  < .01) between the second and third trimester of gestational period as well as nasopharyngeal and oropharyngeal spaces ( P  < .05). High correlation between the development of anterior cranial base and functional areas devoted to speech and swallow is demonstrated ( r : .97). Conclusions: The development of craniofacial structures during foetal period seems to show a close correlation between skeletal features and functional spaces with a peak between the second and third trimester of gestation. MRI images result helpful for the clinician to detect with a sample cephalometric analysis anomalies of skeletal and functional structures during prenatal period.